2015
DOI: 10.1186/s12877-015-0013-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term prognostic value of forced expiratory volume in 1 second divided by height cubed in a prospective cohort of people 80 years and older

Abstract: BackgroundSpirometry-based parameters of pulmonary function such as forced expiratory volume in 1 second (FEV1) have prognostic value beyond respiratory morbidity and mortality. FEV1 divided by height cubed (FEV1/Ht3) has been found to be better at predicting all-cause mortality than the usual standardization as percentage of predicted "normal values" (FEV1%) and its use is independent of reference equations. Yet, limited data are available on the very old adults (80 years and older) and in association to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 48 publications
7
23
0
Order By: Relevance
“… 18 , 34 In addition, FEV 1 as a potential risk marker for adverse health outcomes in older adults can be assessed in spirograms in which plateau of >6 s has not been reached (spirometry quality levels ATS 1–3 are usable for this purpose and were achieved by 96% of participants in the BELFRAIL and 80% of participants in the CRYSTAL study). 4–8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 34 In addition, FEV 1 as a potential risk marker for adverse health outcomes in older adults can be assessed in spirograms in which plateau of >6 s has not been reached (spirometry quality levels ATS 1–3 are usable for this purpose and were achieved by 96% of participants in the BELFRAIL and 80% of participants in the CRYSTAL study). 4–8 …”
Section: Discussionmentioning
confidence: 99%
“…2 , 3 Besides this, spirometry parameters such as forced expiratory volume in 1 s (FEV 1 ) have been found to be predictors of adverse health outcomes such as all-cause mortality, disability and frailty in the older adults. 4–8 Yet, there is still underuse of spirometry for diagnosing respiratory problems, especially in older adults, even though it has become widely available in primary care and hand-held office spirometry is reliable. 9–12 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be reasonably expected that chronic respiratory diseases compromising pulmonary function will trigger or accelerate the development of frailty and/or disability. In very old adults (80 years and older) a poor pulmonary function predicts decline in physical and mental functioning and mortality (Turkeshi et al, 2015). Moreover, exposure to second hand tobacco smoke in non-smoking older adults increases the frequency of frailty (García-Esquinas et al, 2015b).…”
Section: Chronic Respiratory Diseasesmentioning
confidence: 99%
“…An FI can be derived from various types of databases as long as its derivation follows the proposed guideline [ 15 ]. Recent studies convincingly demonstrated that an FI can be derived from data collected with unified instruments from the interRAI suite either with the interRAI Acute Care [ 17 ], interRAI Nursing Homes [ 18 ], or interRAI Home Care [ 19 ]. Aside from FI derivations, scales assessing frailty have also been proposed; among them, the Frailty Scale [ 20 ] built from the interRAI Home Care and the FRAIL-NH scale [ 21 , 22 ] elaborated on the interRAI Nursing Home.…”
Section: Introductionmentioning
confidence: 99%